The problem of competitiveness of young professional psychologists - Saladukha, Aliaksander S.; Fofanova, Galina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is dealed with the problem of competitiveness of graduate psychologists. Differences in the application of the concept of competitiveness in relation to assessing the competencies of graduates of the department of psychology are demonstrated. The requirements of the labor market of Belarus in relation to professional psychologists are considered. Criteria of evaluation of the competitiveness from the point of view of the competence approach are demonstrated. The concept of «key competencies» is considered. The role of cognitive biases in the evaluation of professional psychologists by potential employers is analyzed.